Exploring care from extended family through rural women's accounts of perinatal mental illness – a qualitative study with implications for policy and practice. (November 2020) - Jackson, Katherine; Smart, Deborah; Henderson, Emily J.; Newham, James J.; McGovern, Ruth; Kaner, Eileen; Lingam, Raghu
Abstract: Extended family often have an important role in caring for women experiencing perinatal mental illness; but rural women's perspectives are under-researched. We explored women's experiences of living in rural northern England and receiving care from extended family during periods of perinatal mental illness through 21 qualitative interviews. Key findings were that companionship, practical support - informal childcare and transport, and emotional support were important forms of care - filling gaps in formal service provision. Findings highlight women's needs for support from extended families in rural areas. The rural infrastructure and inequity in formal services can create vulnerability for women. Highlights: Family are a key source of care for rural women during perinatal mental illness. Informal care can help bridge the gap in formal health services in rural areas. Gendered expectations of care are important to women's experiences. Rural women without support from extended family face inequalities.